Analisis Pengendalian Internal Persediaan Bibit Kelapa Sawit Pada Usaha Pembibitan Kelapa Sawit UD. Putri Hijau - Asmarullah .; La Ode Turi; Surianto Ilham; Hasmawati Timpa (CV. ITTC INDONESIA, 2026)
This research is motivated by the importance of internal inventory control in maintaining asset security and supporting the smooth operation of the oil palm seedling nursery business. This research aims to analyze the implementation of internal control over palm oil seed inventory at UD Putri Hijau and assess its alignment with the elements of internal control. The research method used is a descriptive method with a qualitative approach thru observation, interviews, and documentation techniques. The research results show that the internal control of inventory does not fully comply with the elements of internal control. This is evident from the lack of separation of functions between sales, storage, and recording, leading to task duplication. The recording that is done is still simple, only noting the date and the number of seedlings sold without being supported by journals, ledgers, or inventory cards. In addition, periodic physical inventory reconciliation has not been conducted, and there has been no employe training in record-keeping. These findings indicate the need for improvements in the internal inventory control system thru the implementation of function separation, more structured record-keeping, and periodic inventory inspections.